Physical Fitness of PJKR STKIP YPUP Makassar Students Using The Harvard Step Test Method - Agus Sutriawan; Ikadarny Ikadarny; M. Imran Hasanuddin; Retno Farhana Nurulita (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
The purpose of this study was to determine the level of physical fitness of PJKR STKIP YPUP Makassar students who were registered in the even semester of the 2022–2023 academic year. The Harvard Step Test is an instrument used in this study. The implementation is carried out for 5 minutes by going up and down the bench to a height of 50 cm (for men) and 42 cm (for women). Based on the research findings, out of 50 sixth semester students at STKIP YPUP Makassar, 30 people fall into the "Enough" group (70%), and 20 people fall into the "Medium" category (30%). This indicates that the physical health of Semester VI STKIP YPUP Makassar Students for the 2022–2023 Academic Year is still unsatisfactory.